Research Advances in Traditional Chinese Medicine for the Treatment of Alzheimer’s Disease - Cui, Honghong; Hui, Zhenliang; Cao, Rongrong; Zhang, Xiaole (Journal of Contemporary Medical Practice, 2025)
Alzheimer’s disease (AD) is a major neurodegenerative disease that plagues the elderly population, clinically characterized by progressive cognitive decline, neuropsychiatric symptoms, and loss of social function. Epidemiological data from 2020 shows that the number of AD patients aged 60 and above in China has reached approximately 9.83 million. The accelerating trend of population aging has made the disease burden of AD increasingly heavy, posing a public health challenge that cannot be ignored. The etiology of AD remains unclear, and its pathological mechanisms are complex. Characteristic changes include senile plaques formed by extracellular amyloid-β (Aβ) deposition, neurofibrillary tangles mediated by hyperphosphorylated Tau protein, and subsequent synaptic damage and neuronal loss. Current mainstream treatment regimens primarily consist of acetylcholinesterase inhibitors and NMDA receptor antagonists. While these can temporarily alleviate some symptoms, they are unable to halt or reverse the disease process, and are limited by their single-target mechanism of action and the relatively high incidence of adverse effects associated with long-term use. Within the theoretical system of Traditional Chinese Medicine (TCM), AD is classified under categories such as “dementia”, “stupidity”, and “forgetfulness”. Based on the traditional understanding that “the kidney stores essence, produces marrow, and fills the brain,” TCM has accumulated rich experience through long-term clinical practice, gradually forming treatment strategies characterized by a holistic view and syndrome differentiation, involving multi-pathway interventions. A substantial body of research demonstrates that Chinese herbal medicines and their active components exhibit unique advantages of multi-target, systemic regulation in improving cognitive function and delaying disease progression in AD patients, with a good safety profile. This article focuses on three levels—TCM compound formulas, single Chinese herbs, and active components—to systematically review recent relevant experimental research, deeply explore their potential mechanisms of action, and provide valuable ideas and references for the TCM-based prevention and treatment of AD and the development of new drugs.